Atomistic tight-binding theory of CdSe wurtzite nanocrystals - Akkaratch Sukerm (Science Faculty of Chiang Mai University, 2019)
We present a theoretical study on the electronic structures of CdSe wurtzite nanocrystals by means of the tight-binding method and configuration interaction. Based on the single-particle states, several physical properties including density of states (DOS), band gaps, excitonic gaps and electron-hole coulomb interactions are mainly investigated. The observed calculations are mainly sensitive with sizes. The reduction of the single-particle and excitonic gaps is realized owing to the quantum confinement. In addition, the electron-hole coulomb energies are decreased with the increasing sizes. The calculated results are consistent with the other theoretical and experimental data. Finally, our studies elucidate and quantify the importance of sizes in determining the electronic properties of CdSe wurtzite nanocrystals which can aid to design for the further application.